الرحلة الخيالية الى العالم الاخر: معادلاً موضوعياً - السعيدي, عبد الكريم خضير عليوي (Al-Adab Journal, 2019)
This paper seeks cash to stand on the literary works that have been taken from the fictional journey to the other world, which tends to be a scientist for the dead as their theme, as the equivalent objective of the state of the frets and distress experienced by the writer and his community , and then was the purpose of this Charters fictional , are venting what is going on inside them from conflict , caused by the failure of their communities and degradation , loved these writers to be one of the pioneers of reform as they could through what Atqnnouna of Arts , who informed the stories this all they want as saying of things , had previously prevented them from saying the authority controlling ( in all its forms ) in their communities , whether political , religious or social , we chose models of these stories that plague literature different world , including ; trip ( Dionysus ), the god of wine Greek to the world of the dead , which appeared in the play ( Aldvaa ) playwright Greek ( Arstopanis ) , and trip someone you know Zoroastrian Persian name ( Ardaweerav ) to the world of the dead , and are reflected in the story ( Ardaweerav Nameh ), a work of nonfiction ancient Persian , also chose a story ( disciples and storms ) to the son of a martyr Andalusia , as well as the story of a trip (Ibn Qarih ) champion Abe Ala Marri in message of forgiveness , as we have chosen the story ( divine Comedy ), Dante , as well as the story of Mohammed bin Ibrahim Moelhi tagged ( interrupted by Issa bin Hisham ) , as well as a story writer Pakistani Muslim mystic philosopher ( Mohammad Iqbal ) tagged ( Javed Namah ) .